Veterans and Agent Orange: Update 2014 - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
From 1962 to 1971, the US military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the bulk of the herbicides sprayed. The main chemical mixture sprayed was Agent Orange, a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic form of dioxin, was an unintended contaminant generated during the production of 2,4,5-T and so was present in Agent Orange and some other formulations sprayed in Vietnam. Because of complaints from returning Vietnam veterans about their own health and that of their children combined with emerging toxicologic evidence of adverse effects of phenoxy herbicides and TCDD, the National Academy of Sciences was asked to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange, other herbicides used in Vietnam, and the various components of those herbicides, including TCDD. Updated evaluations were conducted every two years to review newly available literature and draw conclusions from the overall evidence. Veterans and Agent Orange: Update 2014 is a cumulative report of the series thus far.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 2012 - Institute of Medicine (The National Academies Press, 2014)
From 1962 to 1971, the US military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the bulk of the herbicides sprayed. The main chemical mixture sprayed was Agent Orange, a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic form of dioxin, was an unintended contaminant generated during the production of 2,4,5-T and so was present in Agent Orange and some other formulations sprayed in Vietnam. Because of complaints from returning Vietnam veterans about their own health and that of their children combined with emerging toxicologic evidence of adverse effects of phenoxy herbicides and TCDD, the National Academy of Sciences (NAS) was asked to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange, other herbicides used in Vietnam, and the various components of those herbicides, including TCDD. Updated evaluations are conducted every two years to review newly available literature and draw conclusions from the overall evidence.Veterans and Agent Orange: Update 2012 reviews peer-reviewed scientific reports concerning associations between health outcomes and exposure to TCDD and other chemicals in the herbicides used in Vietnam that were published in October 2010--September 2012 and integrates this information with the previously established evidence database. This report considers whether a statistical association with herbicide exposure exists, taking into account the strength of the scientific evidence and the appropriateness of the statistical and epidemiological methods used to detect the association; the increased risk of disease among those exposed to herbicides during service in the Republic of Vietnam during the Vietnam era; and whether there exists a plausible biological mechanism or other evidence of a causal relationship between herbicide exposure and the disease.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 2010 - Institute of Medicine (The National Academies Press, 2012)
Because of continuing uncertainty about the long-term health effects of the sprayed herbicides on Vietnam veterans, Congress passed the Agent Orange Act of 1991. The legislation directed the Secretary of Veterans Affairs (VA) to request the Institite of Medicine to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange and other herbicides used in Vietnam to be followed by biennial updates. The 2010 update recommends further research of links between Vietnam service and specific health outcomes, most importantly COPD, tonsil cancer, melanoma, brain cancer, Alzheimer's disease, and paternally transmitted effects to offspring.
Keywords: Health and Medicine

Blue Water Navy Vietnam Veterans and Agent Orange Exposure - Institute of Medicine (The National Academies Press, 2011)
Over 3 million U.S. military personnel were sent to Southeast Asia to fight in the Vietnam War. Since the end of the Vietnam War, veterans have reported numerous health effects. Herbicides used in Vietnam, in particular Agent Orange have been associated with a variety of cancers and other long term health problems from Parkinson's disease and type 2 diabetes to heart disease. Prior to 1997 laws safeguarded all service men and women deployed to Vietnam including members of the Blue Navy. Since then, the Department of Veteran Affairs (VA) has established that Vietnam veterans are automatically eligible for disability benefits should they develop any disease associated with Agent Orange exposure, however, veterans who served on deep sea vessels in Vietnam are not included. These "Blue Water Navy" veterans must prove they were exposed to Agent Orange before they can claim benefits. At the request of the VA, the Institute of Medicine (IOM) examined whether Blue Water Navy veterans had similar exposures to Agent Orange as other Vietnam veterans. Blue Water Navy Vietnam Veterans and Agent Orange Exposure comprehensively examines whether Vietnam veterans in the Blue Water Navy experienced exposures to herbicides and their contaminants by reviewing historical reports, relevant legislation, key personnel insights, and chemical analysis to resolve current debate on this issue.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 11 (2018) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
From 1962 to 1971, the U.S. military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the bulk of the herbicides sprayed. The main chemical mixture sprayed was Agent Orange, a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic form of dioxin, was an unintended contaminant generated during the production of 2,4,5-T and so was present in Agent Orange and some other formulations sprayed in Vietnam. Because of complaints from returning Vietnam veterans about their own health and that of their children combined with emerging toxicologic evidence of adverse effects of phenoxy herbicides and TCDD, the National Academies of Sciences, Engineering, and Medicine was asked to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange, other herbicides used in Vietnam, and the various components of those herbicides, including TCDD. Updated evaluations were conducted every two years to review newly available literature and draw conclusions from the overall evidence. Veterans and Agent Orange: Update 11 (2018) examines peer-reviewed scientific reports concerning associations between various health outcomes and exposure to TCDD and other chemicals in the herbicides used in Vietnam that were published between September 30, 2014, and December 31, 2017, and integrates this information with the previously established evidence database.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 2004 - Institute of Medicine (The National Academies Press, 2005)
Sixth in a series of congressionally mandated studies, this book is an updated review and evaluation of the available evidence regarding the statistical assoication between exposure to herbicides used in Vietnam and various adverse health outcomes suspected to be linked with such exposure. This book builds upon the information contained in the earlier books in the series: Veterans and Agent Orange: Health Effects of Herbicides Used in Vietnam (1994) Veterans and Agent Orange: Update 1996 Veterans and Agent Orange: Update 1998 Veterans and Agent Orange: Update 2000 Veterans and Agent Orange: Update 2002 Veterans and Agent Orange: Herbicides and Dioxin Exposure and Type 2 Diabetes (2000) Veterans and Agent Orange: Herbicide/Dioxin Exposure and Acute Myelogenous Leukemia in the Children of Vietnam Veterans (2002) Veterans and Agent Orange: Update 2004 focuses primarily on scientific studies and other information developed since the release of these earlier books. The previous volumes have noted that sufficient evidence exists to link chronic lymphocytic leukemia, soft-tissue sarcoma, non-Hodgkin’s lymphoma, Hodgkin’s disease, and chloracne with exposure. The books also noted that there is “limited or suggestive” evidence of an association between exposure and respiratory cancers, prostate cancer, multiple myeloma, the metabolic disorder porphyria cutanea tarda, early-onset transient peripheral neuropathies, Type 2 diabetes, and the congenital birth defect spinal bifida in veterans’ children. This volume will be critically important to both policymakers and physicians in the federal government, Vietnam veterans and their families, veterans’ organizations, researchers, and health professionals.
Keywords: Health and Medicine; Conflict and Security Issues

Veterans and Agent Orange: Update 2006 - Institute of Medicine (The National Academies Press, 2007)
From 1962 to 1971, the U.S. military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of U.S. base camps and outlying fire-support bases. In response to concerns and continuing uncertainty about the long-term health effects of the sprayed herbicides on Vietnam veterans, Veterans and Agent Orange provides a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange and other herbicides used in Vietnam. The 2006 report is the seventh volume in this series of biennial updates. It will be of interest to policy makers and physicians in the federal government, veterans and their families, veterans' organizations, researchers, and health professionals.
Keywords: Conflict and Security Issues; Health and Medicine

Veterans and Agent Orange: Update 2008 - Institute of Medicine (The National Academies Press, 2009)
From 1962 to 1971, the U.S. military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of U.S. base camps and outlying fire-support bases. In response to concerns and continuing uncertainty about the long-term health effects of the sprayed herbicides on Vietnam veterans, Veterans and Agent Orange provides a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange and other herbicides used in Vietnam. The 2008 report is the eighth volume in this series of biennial updates. It will be of interest to policy makers and physicians in the federal government, veterans and their families, veterans' organizations, researchers, and health professionals.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 2000 - Institute of Medicine (The National Academies Press, 2001)
Veterans and Agent Orange: Update 2000 examines the state of the scientific evidence regarding associations between diseases and exposure to dioxin and other chemical compounds in herbicides used in Vietnam. It is the fourth in a series of comprehensive reviews of epidemiologic and toxicologic studies of the agents used as defoliants during the Vietnam War. Over forty health outcomes in veterans and their children are addressed. Among the report's conclusions is that there is sufficient evidence of a link between exposure and the development of soft-tissue sarcoma, non-Hodgkin's lymphoma, Hodgkin's disease, and chloracne in veterans. Additionally, it found that scientific studies offer "limited or suggestive" evidence of an association with other diseases in veterans—including Type 2 diabetes, respiratory cancers, prostate cancer, multiple myeloma and some forms of transient peripheral neuropathy—as well as the congenital birth defect spina bifida in veterans' children.
Keywords: Health and Medicine; Conflict and Security Issues

Veterans and Agent Orange: Update 2002 - Institute of Medicine (The National Academies Press, 2003)
This book updates and evaluates the available scientific evidence regarding statistical associations between diseases and exposure to dioxin and other chemical compounds in herbicides used in Vietnam, focusing on new scientific studies and literature.
Keywords: Health and Medicine; Conflict and Security Issues

Veterans and Agent Orange: Herbicide/Dioxin Exposure and Type 2 Diabetes - Institute of Medicine (The National Academies Press, 2000)
In response to the concerns voiced by Vietnam veterans and their families, Congress called upon the National Academy of Sciences (NAS) to review the scientific evidence on the possible health effects of exposure to Agent Orange and other herbicides. This call resulted in the creation of the first NAS Institute of Medicine Committee to Review the Health Effects in Vietnam Veterans of Exposure to Herbicides in 1992. The committee published its initial findings in the 1994 report Veterans and Agent Orange: Health Effects of Herbicides Used in Vietnam. This report is the result of a 1999 request from the Department of Veterans Affairs (DVA) under the aegis of the Veterans and Agent Orange research program. Specifically, DVA asked the committee to examine evidence regarding the association, if any, between Type 2 diabetes and exposure to dioxin and other chemical compounds in herbicides used in Vietnam. Veterans and Agent Orange: Herbicide/Dioxin Exposure and Type 2 Diabetes reviews the scientific evidence regarding the association, if any, between Type 2 diabetes1 and exposure to dioxin2 and other chemical compounds in herbicides used in Vietnam. This report examines, to the extent that available data permitted meaningful determinations, (1) whether a statistical association with herbicide exposure exists, taking into account the strength of the scientific evidence and the appropriateness of the statistical and epidemiologic methods used to detect the association; (2) the increased risk of the disease among those exposed to herbicides during Vietnam service; and (3) whether there is a plausible biological mechanism or other evidence of a causal relationship between herbicide exposure and the disease.
Keywords: Health and Medicine

Veterans and Agent Orange: Length of Presumptive Period for Association Between Exposure and Respiratory Cancer - Institute of Medicine (The National Academies Press, 2004)
From 1962 to 1971, US military forces sprayed herbicides over Vietnam to strip the thick jungle canopy that helped conceal opposition forces, to destroy crops that enemy forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the majority of the herbicides sprayed. Agent Orange was a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD, one form of dioxin) was an unintended contaminant from the production of 2,4,5-T and was present in Agent Orange and some other formulations sprayed in Vietnam.In 1991, because of continuing uncertainty about the long-term health effects on Vietnam veterans of the herbicides sprayed, Congress passed Public Law 102-4, the Agent Orange Act of 1991. In response to the request from the VA, IOM extended the service of the Committee to Review the Health Effects in Vietnam Veterans of Exposure to Herbicides that was responsible for Update 2002 to address the question of presumptive period and respiratory cancer. The charge to the committee was to undertake a review and evaluation of the evidence regarding the period between cessation of exposure to herbicides used in Vietnam and their contaminants (2,4-D, 2,4,5-T and its contaminant TCDD, cacodylic acid, and picloram) and the occurrence of respiratory cancer.
Keywords: Health and Medicine; Conflict and Security Issues

Characterizing Exposure of Veterans to Agent Orange and Other Herbicides Used in Vietnam: Interim Findings and Recommendations - Institute of Medicine (The National Academies Press, 2003)
From 1962 to 1971, US military forces sprayed more than 19 million gallons of herbicides over Vietnam to strip the thick jungle canopy that helped conceal opposition forces, to destroy crops that enemy forces might depend on, and to clear tall grass and bushes from around the perimeters of US base camps and outlying fire-support bases. Most large-scale spraying operations were conducted from airplanes and helicopters, but herbicides were also sprayed from boats and ground vehicles, and by soldiers wearing back-mounted equipment. After a scientific report concluded that a contaminant of one of the primary chemicals used in the herbicide called Agent Orange could cause birth defects in laboratory animals, US forces suspended use of the herbicide; they subsequently halted all herbicide spraying in Vietnam in 1971. At the request of the Veteran's Administration, the Institute of Medicine established a committee to oversee the development and evaluation of models of herbicide exposure for use in studies of Vietnam veterans. That committee would develop and disseminate a request for proposals (RFP) consistent with the recommendations; evaluate the proposals received in response to the RFP and select one or more academic or other nongovernmental research groups to develop the exposure reconstruction model; provide scientific and administrative oversight of the work of the researchers; and evaluate the models developed by the researchers in a report to VA, which would be published for a broader audience. Characterizing Exposure of Veterans to Agent Orange and Other Herbicides Used in Vietnam is the IOM's report that evaluates models of herbicide reconstruction to develop and test models of herbicide exposure for use in studies of Vietnam veterans.
Keywords: Health and Medicine

Characterizing Exposure of Veterans to Agent Orange and Other Herbicides Used in Vietnam: Final Report - Institute of Medicine (The National Academies Press, 2003)
Keywords: Health and Medicine

Veterans and Agent Orange: Herbicide/Dioxin Exposure and Acute Myelogenous Leukemia in the Children of Vietnam Veterans - Institute of Medicine (The National Academies Press, 2002)
In 2001, in response to a request by the U.S. Department of Veterans Affairs (DVA), the Institute of Medicine (IOM) called together a committee to conduct a review of the scientific evidence regarding the association between exposure to dioxin and other chemical compounds in herbicides used in Vietnam and acute myelogenous leukemia in the offspring of Vietnam veterans. Based on the scientific evidence reviewed in this report, the committee finds there is inadequate or insufficient evidence to determine if an association exists between exposure to the herbicides used in Vietnam or their contaminants and acute myelogenous leukemia (AML) in the children of Vietnam veterans. This is a change in classification from the recent Veterans and Agent Orange: Update 2000 report, which found limited/suggestive evidence for such an association.
Keywords: Health and Medicine; Conflict and Security Issues

Post-Vietnam Dioxin Exposure in Agent Orange-Contaminated C-123 Aircraft - Institute of Medicine (The National Academies Press, 2015)
From 1972 to 1982, approximately 1,500-2,100 US Air Force Reserve personnel trained and worked on C-123 aircraft that had formerly been used to spray herbicides in Vietnam as part of Operation Ranch Hand. After becoming aware that some of the aircraft on which they had worked had previously served this purpose, some of these AF Reservists applied to the US Department of Veterans Affairs (VA) for compensatory coverage under the Agent Orange Act of 1991. The Act provides health care and disability coverage for health conditions that have been deemed presumptively service-related for herbicide exposure during the Vietnam War. The VA denied the applications on the basis that these veterans were ineligible because as non-Vietnam-era veterans or as Vietnam-era veterans without "boots on the ground" service in Vietnam, they were not covered. However, with the knowledge that some air and wipe samples taken between 1979 and 2009 from some of the C-123s used in Operation Ranch Hand showed the presence of agent orange residues, representatives of the C-123 Veterans Association began a concerted effort to reverse VA's position and obtain coverage. At the request of the VA, Post-Vietnam Dioxin Exposure in Agent Orange-Contaminated C-123 Aircraft evaluates whether or not service in these C-123s could have plausibly resulted in exposures detrimental to the health of these Air Force Reservists. The Institute of Medicine assembled an expert committee to address this question qualitatively, but in a scientific and evidence-based fashion. This report evaluates the reliability of the available information for establishing exposure and addresses and places in context whether any documented residues represent potentially harmful exposure by characterizing the amounts available and the degree to which absorption might be expected. Post-Vietnam Dioxin Exposure rejects the idea that the dioxin residues detected on interior surfaces of the C-123s were immobile and effectively inaccessible to the Reservists as a source of exposure. Accordingly, this report states with confidence that the Air Force Reservists were exposed when working in the Operation Ranch Hand C-123s and so experienced some increase in their risk of a variety of adverse responses.
Keywords: Health and Medicine

Achieving Whole Health: A New Approach for Veterans and the Nation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Whole health is physical, behavioral, spiritual, and socioeconomic well-being as defined by individuals, families, and communities. Whole health care is an interprofessional, team-based approach anchored in trusted relationships to promote well-being, prevent disease, and restore health. It aligns with a person's life mission, aspiration, and purpose. It shifts the focus from a reactive disease-oriented medical care system to one that prioritizes disease prevention, health, and well-being. It changes the health care conversation from "What’s wrong with you?" to "What matters to you?"The Department of Veterans Affairs (VA), the Samueli Foundation, and the Whole Health Institute commissioned the National Academies of Sciences, Engineering, and Medicine to establish a committee to provide guidance on how to fill gaps and create processes to accelerate the transformation to whole health care for veterans, both inside and outside the VA system, and the rest of the U.S. population. The resulting report presents findings and recommendations that provide a roadmap for improving health and well-being for veterans and the nation.
Keywords: Health and Medicine

Use of Recycling Agents in Asphalt Concrete Mixtures - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Although the use of recycled asphalt materials (RAM) in new asphalt mixtures can reduce the amount of virgin and nonrenewable materials required and increase the rutting resistance of pavements, it may also compromise cracking resistance. To mitigate this issue, asphalt mixtures containing RAM may require the use of a softer binder or recycling agent (RA).The TRB National Cooperative Highway Research Program's NCHRP Synthesis 586: Use of Recycling Agents in Asphalt Concrete Mixtures documents current state department of transportation (DOT) practices and procedures related to the use of RAs in asphalt mixtures containing RAM.
Keywords: Transportation and Infrastructure

Review of the Department of Veterans Affairs Presumption Decision Process - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Department of Veterans Affairs (VA) provides health care and other benefits to eligible veterans with physical and mental injuries or illnesses (conditions) related to their military service. When the scientific information needed to connect a veterans service or a particular military exposure with their diagnosed condition is nonexistent, impossible to obtain, or incomplete, VA may make a presumption of service connection using a formalized decision process. In 2022, VA instituted a series of changes intended to ensure the presumption decision process was more scientifically based, fair, consistent, transparent, timely, and veteran-centric. The PACT Act of 2022 called for a National Academies committee to review the VA revised process document used to identify medical conditions to evaluate for presumption status, the factors that such an evaluation entails, and the governance process for the review and approval of a presumption recommendation. This resulting report, Review of the Department of Veterans Affairs Presumption Decision Process, contains the committee findings, conclusions, and recommendations.
Keywords: Health and Medicine

Improving Access to High-Quality Mental Health Care for Veterans: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mental and behavioral health care needs of Americans, including veterans, have substantially grown over the past few decades. As the nations largest provider of mental health care, the U.S. Department of Veterans Affairs (VA) faces some of the greatest challenges in meeting the mental health care needs of its population. These challenges are exacerbated by a shrinking mental health care workforce and provider shortages in low-income and rural communities. To address these challenges, and at the request of VA, the National Academies of Sciences, Engineering, and Medicine Forum on Mental Health and Substance Use Disorders held a public workshop on Improving Access to High-Quality Mental Health Care for Veterans to explore the U.S. landscape for mental health care services, including telehealth services. The workshop considered ways to improve veterans timely access to high-quality care for mental health conditions. In particular, it explored internal and external best practices for three critical needs for mental health access (known as tripartite access in VA): urgent/crisis, engagement, and sustained access. This proceedings document summarizes discussions at the workshop.
Keywords: Health and Medicine